Myxoid liposarcoma in the extremities: A case report - Atqiaee, Khashayar; Lotfollahzadeh, Saran; Mirshemirani, Alireza (Indian Journal of Case Reports, 2018)
Liposarcoma is among the most common sarcomas in the adult population. On the contrary, their incidence in the pediatric population is rare. The most common subtype affecting extremities is the myxoid liposarcoma. The preferred method of surgery for the limb myxoid liposarcoma is the limb-preserving surgeries. In the current study, we report the case of a patient who was affected by myxoid liposarcoma and who underwent conservative management with the impression of lipoma several months before the definite diagnosis was obtained. After diagnosis, he underwent radical resection in a single procedure and was referred to the oncology ward for further adjunct treatment.